Groundwork of the metaphysics of morals - Kant, Immanuel, 1724-1804; Gregor, Mary J.; Timmermann, Jens (Cambridge : Cambridge University Press, 2012)
Published in 1785, Immanuel Kant's Groundwork of the Metaphysics of Morals ranks alongside Plato's Republic and Aristotle's Nicomachean Ethics as one of the most profound and influential works in moral philosophy ever written. In Kant's own words, its aim is to identify and corroborate the supreme principle of morality, the categorical imperative. He argues that human beings are ends in themselves, never to be used by anyone merely as a means, and that universal and unconditional obligations must be understood as an expression of the human capacity for autonomy and self-governance. As such, they are laws of freedom. This volume contains Mary Gregor's acclaimed translation of the text into English, revised by Jens Timmermann, and an accessible, updated introduction by Christine Korsgaard.
Preface to the revised edition -- Introduction -- Chronology -- Groundwork of the Metaphysics of morals. Preface ; First section: Transition from common to philosophical moral rational cognition ; Second section: Transition from popular moral philosophy to the metaphysics of morals ; Third section: Transition from the metaphysics of morals to the critique of pure practical reason -- Selected glossary.
Title from publisher's bibliographic system (viewed on 18 Jul 2016).
Keywords: elektronické knihy; electronic books; Ethics -- Early works to 1800.